The "No Wrong Door" Approach to HIV Testing: Results From a Statewide Retail Pharmacy–Based HIV Testing Program in Virginia, 2014-2016. (November 2018) - Collins, Bryan; Bronson, Heather; Elamin, Fatima; Yerkes, Lauren; Martin, Elaine
Objective: As part of the Care and Prevention in the United States Demonstration Project (2012-2016), which aimed to reduce HIV-related morbidity and mortality among racial/ethnic minority groups in 8 states, the Virginia Department of Health (VDH) funded Walgreens to provide HIV testing in retail pharmacies in areas with large racial/ethnic minority communities and high rates of poverty. We describe this program and summarize its outcomes. We hypothesized that (1) offering walk-in HIV testing outside of traditional business hours and alongside other point-of-care tests in retail pharmacies would increase rates of first-time testers and (2) using data on social determinants of health associated with higher rates of HIV infection to locate test sites would increase the identification of people who were previously undiagnosed. Methods: Using 2010 US Census data and 2007-2011 five-year population estimates from the American Community Survey, VDH selected 32 Walgreens stores located in census tracts where at least 30% of the population was black and/or Hispanic/Latino and/or where at least 20% of the population was living at or below the federal poverty level. Pharmacists administered the INSTI HIV-1/HIV-2 Rapid Antibody Test. Clients with a reactive test result were linked to confirmatory testing and medical care. Results: Between June 1, 2014, and September 29, 2016, Walgreens pharmacists performed HIV tests on 3630 clients, of whom 1668 (46.0%) had either never been tested or were unsure if they had been tested. Of all clients tested, 30 (0.8%) had a reactive test result. Of 26 clients who also had positive confirmatory testing, 22 (84.6%) were linked to care. The mean cost per person tested was $41.79, and the mean cost per reactive result was $5057. Conclusions: Retail pharmacies may be an effective venue for those who have never been tested for HIV to access HIV testing, particularly if the pharmacies are located in priority areas or where community-based organizations are unable to operate.